Ações de gestão do conhecimento e informação na Procuradoria-Geral Federal. - Costa, Eduardo de Albuquerque (2013)
This research has the main objective to investigate the actions of knowledge and information management in the Federal Attorney General from the perspective of their contribution to the organization learning in this institution. Therefore, the present work aims, with as many details as possible, to identify the actions of knowledge and information management in the Federal Attorney General, verify if there are internal programs in this institution specifies to this purpose, describe the programs and actions of knowledge and information management and analyze their contribution to the organizational learning, as well as investigate the contribution to the formation of intellectual capital, arising from the initiatives of knowledge and information management.